Quantum Chemical Investigation of Molecular Structure, Thermal, Electronic Properties and Reactivity of propargyl 2-bromoisobutyrate - Hekim, Seda; Pekdemir, Mustafa Ersin (TUBITAK, 2022)
To predict reactivity and reactive sites on the propargyl 2-bromoisobutyrate molecule, several global and local reactivity descriptors have been computed. All calculations have been made through a computational study based on density functional theory (DFT/B3LYP) using a basis set LanL2DZ. The stability of the molecule has been investigated using the natural bond orbital (NBO) analysis. The highest occupied molecular orbital (HOMO) energies, the lowest unoccupied molecular orbital (LUMO) energies have been calculated and the electronic properties depending on HOMO-LUMO energies were determined. Also, the thermodynamic properties of the title compound were studied. The electron density-based local reactivity descriptors such as the Fukui functions have been calculated to explain the chemical selectivity or reactivity site in the molecule. © 2022, TUBITAK. All rights reserved.
Propargil 2-bromoizobütiratın Moleküler Yapısının, Termal, Elektronik Özelliklerinin ve Reaktivitesinin Kuantum Kimyasal İncelenmesi
Keywords: B3LYP; DFT; HOMO and LUMO orbital energies; LanL2DZ basis set; NBO; Propargyl 2-bromoisobutyrate